2012
DOI: 10.3184/174751912x13352842814921
|View full text |Cite
|
Sign up to set email alerts
|

Boric Acid Catalysed Synthesis of α-Aminonitriles by a Three-Component Reaction at Room Temperature

Abstract: A simple, efficient, and cost-effective method has been developed for the one-pot, three-component condensation reaction of trimethylsilyl cyanide, aldehydes and aromatic amines using boric acid as a heterogeneous solid acid catalyst, under solvent-free conditions. α-Aminonitriles were synthesised relatively quickly in good yields at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Considering the biomedical applications of αaminonitrile derivatives and in the perpetuation of the development of practical, convenient and environmentally-friendly procedures for one-pot multi-component reactions, [23][24][25][26][27] we were prompted to exploit the catalytic potential of sodium dihydrogen phosphate for a facile and efficient three-component synthesis of functionalized αaminonitriles through a multicomponent reaction of aldehyde, amine, and TMSCN (Scheme 1). Our literature survey at this stage revealed that sodium dihydrogen phosphate (NaH 2 PO 4 ) has not been utilized for the synthesis of α-aminonitriles.…”
Section: Introduction *mentioning
confidence: 99%
“…Considering the biomedical applications of αaminonitrile derivatives and in the perpetuation of the development of practical, convenient and environmentally-friendly procedures for one-pot multi-component reactions, [23][24][25][26][27] we were prompted to exploit the catalytic potential of sodium dihydrogen phosphate for a facile and efficient three-component synthesis of functionalized αaminonitriles through a multicomponent reaction of aldehyde, amine, and TMSCN (Scheme 1). Our literature survey at this stage revealed that sodium dihydrogen phosphate (NaH 2 PO 4 ) has not been utilized for the synthesis of α-aminonitriles.…”
Section: Introduction *mentioning
confidence: 99%